Geochemistry of Ophiolite Complex in North Konawe, Southeast Sulawesi - Irzon, Ronaldo; Baharuddin (EKSPLORIUM, 2016)
Southeast Sulawesi is crosscutted by Lasolo Fault into two geological provinces: Tinondo and Hialu. Tinondo Geological Province is occupied largely by Ophiolite Complex in the northern part of Southeast Arm of Sulawesi. No study was conducted in relation to the geochemistry composition of Ophiolite Complex in North Konawe Regency. The aim of this study is to describe the ultramafic rock of the Ophiolite Complex in North Konawe Regency using field, geochemical, and petrographical analysis. Megascopically, the selected nine samples are described as greyish to blackish and fine to medium grains ultramafic rocks, which consist of pyroxene and olivine. Microscope, X-Ray Fluorescence (XRF), and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) devices were used to obtain both petrography and geochemistry data. Major oxides data confirm that the selected samples are classified into ultramafic rocks as SiO2, MgO, and Fe2O3T are the most abundant oxides. The studied samples presumably came from arc tholeiitic environment tectonic setting. Ultramafic rocks often contain promising economic metals whereas the average numbers of Ni, Mn, Cr, and Co of this study are 2,675; 1,074; 2,386; and 117 ppm respectively. The rocks are generally enriched in high field strength elements whilst rare earth elements value are low, ranging from 2.11 to 7.10 ppm. Microscopically, samples can be classified into three groups: olivine-hornblende pyroxenite, lherzolite, and olivine websterite. Geochemical data describes more about the discriminant analysis of the groups.